1997
DOI: 10.1103/physrevlett.78.4518
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Control of Cardiac Alternans

Abstract: A dynamic control technique was used to suppress a cardiac arrhythmia called an alternans rhythm in a piece of dissected rabbit heart. Our control algorithm adapted to drifting system parameters, making it well suited for the control of physiological rhythms. Control of cardiac alternans rhythms may have important clinical implications since they often precede serious cardiac arrhythmias and are a harbinger of sudden cardiac death.[S0031-9007 (97)03337-1] PACS numbers: 87.22. -q, 05.45. + b, 07.05.Dz, 87.10.+e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
156
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(157 citation statements)
references
References 22 publications
1
156
0
Order By: Relevance
“…Initial work in that direction showed that closed-loop feedback methods could be used to suppress a type of alternans (known as atrioventricular-nodal conduction alternans) with period-doubling dynamics that are related to those of APD alternans [10][11][12][13]. More recently, it was shown that a related control method could terminate APD alternans in isolated frog hearts [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Initial work in that direction showed that closed-loop feedback methods could be used to suppress a type of alternans (known as atrioventricular-nodal conduction alternans) with period-doubling dynamics that are related to those of APD alternans [10][11][12][13]. More recently, it was shown that a related control method could terminate APD alternans in isolated frog hearts [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…DFC has been successfully applied to many systems, including the stabilization of coherent modes of laser [5,6]; cardiac systems, [7,8], controlling friction, [9]; chaotic electronic oscillators, [10,11]; chemical systems, [12]. To overcome the limitations of DFC, several modifications have been proposed, [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, we refer to R as the history parameter for the ETDAS method. We remark that variants of the special case of ETDAS in which R = 0 (i.e., A n+1 is directly influenced only by the most recent APD value, A n ) have been used for experimental control of alternans both in vivo [14] and in vitro [7,17,28].…”
Section: The Etdas Methodsmentioning
confidence: 99%
“…Notably, by writing the ADIC scheme in an apparently different but equivalent way, one finds that the ADIC scheme is actually a special case of ETDAS and the important advantages of ADIC are shared by all ETDAS schemes. ETDAS has several noteworthy features, such as: (i) the control domain (i.e., the set of all possible parameter choices for which control successfully suppresses alternans) is large; (ii) various special cases of ETDAS have been used to control AV-nodal conduction time alternans in humans in vivo [14] as well as APD alternans in canines [7], frogs [17] and rabbits [28] in vitro; (iii) ETDAS is amenable to experimental setup and has already been used for chaos control in physical systems [24,29]; (iv) it is possible to restrict the ETDAS parameters to achieve control while allowing only shortening of BCL; (v) the additional freedom gained by using ETDAS as opposed to restrictive cases such as ADIC allows the experimenter to choose parameters in such a way that sensitivity to background noise is reduced; and (vi) because ETDAS has been studied for over a decade, one may exploit prior mathematical analysis [23,24] as a guide for choosing system parameters that lead to successful control of alternans.…”
Section: Introductionmentioning
confidence: 99%